Specification Acupuncture Points Li4 and Sp6 in Postpartum Sectio Caesarea Pain - Nurul Azizah; Rafhani Rosyidah; Jamilatur Rohmah (EMBRIO: Jurnal Kebidanan, 2023)
Postoperative pain can affect the postpartum SC's mobility, and the physical healing process after surgery can also trigger physiological stress and anxiety due to wound pain. The presence of side effects from analgesic use prompts the exploration of non-pharmacological treatments as an alternative for pain management in post-SC clients, as they are considered to have low side effects. Acupuncture, as one of the non-pharmacological complementary therapies, has been developed to address pain. This research aims to identify the Specific Points of Acupuncture, Li4 and Sp6, in Postpartum Cesarean Section (SC) Pain. The research design employed a quasi-experimental clinical approach, specifically a non-equivalent pre-posttest with a control group. This involved identifying pain reduction before and 24 hours after administering acupuncture intervention at specific points, LI4 and SP6, for a duration of 30 minutes. The study included a total of 34 participants in both the treatment and control groups. The research was conducted at Airlangga University Hospital in Surabaya. The subjects of the study were patients who met the inclusion criteria. The Pain Numeric Rating Scale was used as the research instrument. Statistical analysis involved employing one-way ANOVA to observe the mean change in values between the pre-test and post-test within each group. The administration of acupuncture therapy targeting points LI4 and SP6 in this study proved effective in reducing postpartum SC pain compared to the control group. In future research, further investigation could be conducted to identify changes in chemical reactions within the body following acupuncture treatment.